THE ANTIBACTERIAL ACTIVITY OF A COMBINATION OF YOGURT AND SAFFRON EXTRACT AGAINST Staphylococcus aureus - Fitriany, Erna; Priyoherianto, Andri; Iswandi; Deny Budi L.; Didik Andito (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Background: Yogurt is a fermented milk product that has a positive influence on health because of its bioactive proteins, vitamins, minerals, improved bioavailability, and hydrolyzed carbohydrates. Yogurt contains lactic acid bacteria that can inhibit the growth of Staphylococcus aureus. Objectives: This study aimed to determine the addition of Saffron Extract to yogurt against Staphylococcus aureus and to test its antibacterial activity against Staphylococcus aureus. Material and Methods: The study was an experimental study with various concentrations of Saffron extract (25%; 50%; 75%; and 100%) that were added to the cow milk-based yogurt. The mixed saffron extract (MSE) was centrifuged to obtain the supernatant. The antibacterial activity was evaluated using the disc diffusion method. based on the strength of the zone of inhibition. The negative control was plain yogurt and the positive control was chloramphenicol. Results: Phytochemical screening was used to observe flavonoids, steroids, phenols, saponins, and tannins in the saffron extract. MSE showed antibacterial activity against S. aureus with inhibition zones of 5.19 ± 0.39 mm, 5,77± 0.78 mm, 7,98± 1.43 mm, 9,01± 1.48 mm for, concentration of 25%, 50%, 75%, and 100%, respectively. The positive control inhibition zone was 46.61 mm and the negative control was 4.98± 0.39 mm. Conclusions: Saffron extract added to yogurt at concentrations of 75% and 100% inhibited the growth of S. aureus. Keywords: Saffron extract, S. aureus, Yogurt